Pengembangan Modul Resiliensi Untuk Mahasiswa Generasi Z - Karunia Sari, Diana; Setyadi, Dendy (Jurnal Bimbingan dan Konseling Pandohop, 2024)
The purpose of this research is to develop a resilience module product for Generation Z students that is practical and feasible to use to provide information about resilience to students and to determine the feasibility of the resilience module from the responses of Generation Z students in the Guidance and Counseling Study Program of Sanata Dharma University. This research uses the Research and Development method developed by Borg and Gall. This research was modified into 5 stages, namely: research and information gathering, planning, initial product format development, initial product validation, and product revision. This research was assessed by three expert validators, namely material expert validators, media expert validators, and assessed by user validators, namely students. This research produced a module book entitled "Gen-Z Student Resilience Module". The assessment results from each validator, namely the material expert validator of 90% (very feasible), the first media expert validator of 96.77% (very feasible), the second media expert validator of 89.51% (very feasible), and the user validator, namely students of 90% (very feasible). Based on the validation results, it can be concluded that the Gen-Z resilience module book is categorized as very feasible with an average percentage of 91%. The Gen-Z student resilience module book is expected to be further tested by further researchers so that it can be used effectively, and this research is also expected to be implemented at other universities.